Study on the Use of On-Grid Rooftop Solar Power Plants in Helping to Reduce Electrical Energy Consumption at LPI. Dayah Ulee Titi Foundation - Teuku Zulfadli (Politeknik Negeri Lhokseumawe, 2022)
Solar power plant is a generator that converts solar energy into electrical energy through solar module media. The utilization of solar energy is very volatile to changes in the weather, causing the production of electrical energy to be disrupted or not optimal. For that, we need a system that can maximise energy from solar modules, namely the on-grid rooftop solar power plants system with State Electricity Company (PLN) network. Currently, on-grid rooftop solar power plants has been widely used, one of which is the Islamic Education Institute (LPI) of the Dayah Ulee Titi Foundation. The on-grid rooftop solar power plants at Dayah Ulee Titi is assisted by the Ministry of Energy and Mineral Resources (ESDM) and has been operating since January 2020. However, based on electricity account data from January 2020 to March 2021, it has not shown a significant decrease in the value of the monthly electricity bill. Its export kWh is still very low. This study aims to determine the cause of the non-maximum power supply and the use of the Rooftop solar power plant in Dayah Ulee Titi. The benefit of this research is to reduce the electricity consumption cost in Dayah Ulee Titi so that it can help reduce its operational costs. As a result, the tilt angle of the solar panels installed on Dayah Ulee Titi is considered very suitable and efficient, which is 32.60. The measurement results using the Automatic Meter Reading (AMR) kWh meter in June 2021 found that the total value of export kWh was 6533.26 kWh, while the total imported kWh value from solar power plant to PLN was 44.13 kWh. From May s.d. To September 2021, the Rooftop solar power plant at Dayah Ulee Titi can produce an average of 1246.3 kWh of electrical energy so that it can reduce electricity consumption (kWh savings) from PLN by an average of 25.2%.